2015
DOI: 10.1016/j.polymertesting.2015.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of functionalized graphene oxide/carbon fiber/epoxy nanocomposites

Abstract: a b s t r a c tGraphene oxide (GO) was functionalized using three different diamines, namely ethylenediamine (EDA), 4,4 0 -diaminodiphenyl sulfone (DDS) and p-phenylenediamine (PPD) to reinforce an epoxy adhesive, with the aim of improving the bonding strength of carbon fiber/epoxy composite. The chemical structure of the functionalized GO (FGO) nanosheets was characterized by elemental analysis, FT-IR and XRD. Hand lay-up, as a simple method, was applied for 3-ply composite fabrication. In the sample preparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(42 citation statements)
references
References 24 publications
(28 reference statements)
2
39
0
1
Order By: Relevance
“…Similar results have also been reported in previous studies. Ashori et al [24] investigated the effect of functionalized graphene oxide (FGO) on the properties of carbon fiber (CF)/epoxy composites and found that the FGO creates difficulties to pull out carbon fibers from the matrix. Their SEM micrographs showed that the addition of FGO miniaturized the gaps between the pulled-out carbon fibers and the epoxy matrix.…”
Section: Surface Microstructurementioning
confidence: 99%
“…Similar results have also been reported in previous studies. Ashori et al [24] investigated the effect of functionalized graphene oxide (FGO) on the properties of carbon fiber (CF)/epoxy composites and found that the FGO creates difficulties to pull out carbon fibers from the matrix. Their SEM micrographs showed that the addition of FGO miniaturized the gaps between the pulled-out carbon fibers and the epoxy matrix.…”
Section: Surface Microstructurementioning
confidence: 99%
“…The flexural The improvement of flexural strength should be attributed to the enhancement of the interfacial adhesion between the CFs and MAH-GO (or GO). The enhanced interfacial adhesion allows better load transfer from the resin matrix to the CFs [2,23]. Another possible reason is the synergistic effects [24] of microscopic CFs and nanoscale MAH-GO (or GO).…”
Section: Flexural Properties Of Cf/bmi Compositesmentioning
confidence: 99%
“…Carbon fiber (CF) reinforced polymer composites have been widely used in aerospace, automobiles, constructions and other industry fields because of their excellent mechanical properties, such as high specific strength, specific modulus and damping capacity [1][2][3]. As well known, the mechanical properties of fiber reinforced composites are largely dominated by the fiber-matrix interfacial adhesion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong van der Waals force makes graphene attracts each other, and thus induces the reaggregation of graphene. 19,20 To solve this problem, surface functionalization of graphene is commonly used. [21][22][23][24] Without forming actual chemical bonds, surfactant functionalization connects the graphene and functional groups by only physical adsorption, which involves the advantage of easy processability and high de-bundling effectiveness.…”
Section: Introductionmentioning
confidence: 99%